2019
DOI: 10.21776/ub.jtapro.2019.020.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Nilai Koefisien Cerna Protein Kasar dan Total Digestible Nutrien (TDN) Kambing Bligon Betina yang Mendapat Suplemen Mengandung Protein Tidak Terdegradasi

Abstract: ABSTRAKPemanfaatan protein ransum oleh ternak ruminansia untuk meningkatkan produksi tidak dapat optima dengan adanya mikrobia rumen. Keadaan ini menyebabkan menurunnya nilai hayati protein pakan. Untuk itu, perlu dilakukan perlindungan protein pakan. Salah satu yang dilakukan dengan penambahan bahan kimia misalnya formaldehida. Tujuan dari penelitian ini yaitu mengetahui nilai konsumsi, koefisien cerna dan nutrien tercerna protein kasar serta TDN kambing bligon betina yang mendapat suplemen mengandung protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…It was associated with crude protein and extracted ether from FNG, which was also higher than ISS and LSS. Crude protein digestibility depends on the source and protection of the protein source [ 30 ]. The low digestibility of nitrogen-free extract and total digestible nutrient value was related to crude fiber content [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was associated with crude protein and extracted ether from FNG, which was also higher than ISS and LSS. Crude protein digestibility depends on the source and protection of the protein source [ 30 ]. The low digestibility of nitrogen-free extract and total digestible nutrient value was related to crude fiber content [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Setiyawan et al [ 30 ] reported that a female Bligon goats weighing 16 kg, aged 1.5–2 years, showed ADWG of 30.8–61.3 gm/head. Bligon goats fed with complete fermentation feed for 1 week and 2 weeks showed increases in body weight of 3.12 and 3.30 gm/head/day, respectively [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low TDN of each treatment (Table 1) caused the low degradability of macronutrients. Setiyawan et al (2019) state that the TDN ration for goats is at least 65%.…”
Section: Macronutrient Digestibilitymentioning
confidence: 99%